Immunohistochemical analysis of pyroptosis‐related protein expression in IgG4‐related sialadenitis. (9th March 2022) - Pu, Jiao; Jia, Mengying; Shi, Wei; Hu, Lulu; Wang, Fang; Niu, Yaqi; Tong, Qiaoying; Gong, Zhongcheng
Abstract: Background: NLRP3 (NOD‐, LRR‐ and pyrin domain‐containing protein 3)‐induced pyroptosis is involved in the development of a variety of autoimmune diseases, but its role in IgG4‐related sialadenitis (IgG4‐RS) is unclear. Methods: Salivary gland tissues from 19 patients with IgG4‐RS were designated the experimental group, and peritumoral tissues from 20 patients with benign salivary gland tumours were designated the control group. The cell morphology and fibrosis in the IgG4‐RS samples were observed by haematoxylin‐eosin (H&E) and Masson trichrome (MT) staining. Immunohistochemical (IHC) staining was used to determine pyroptosis‐related proteins (NLRP3, ASC (apoptosis‐associated speck‐like protein containing a CARD), Caspase‐1, GSDMD (gasdermin family members, including digestive dermatin D), interleukin 1β (IL‐1β), and interleukin 18 (IL‐18)) expression levels. Results: Increased lymphoid follicle proliferation, germinal centre plasma cell infiltration, and irregular fibrosis were observed in the experimental group compared with the control group. The NLRP3, ASC, Caspase‐1, GSDMD, IL‐1β, and IL‐18 levels were significantly higher in the experimental group than in the control group ( p  < 0.0001). Conclusion: This study suggested that pyroptosis‐related proteins might be involved in IgG4‐RS pathogenesis. However, the specific cellular pathway involved and whether multiple cell death pathways contribute to the occurrence of IgG4‐RS still need to be further studied.